Synthesis of Silica-PEG By Physically Coating With PEG 4000 For Absorption of Ion Nitrate - Aster Rahayu; Maryudi Maryudi; Joni Aldilla Fajri; Lee Wah Lim; Nuraini Nuraini (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Abstract: All production activities will eventually produce waste, especially liquid waste. The nitrate ion (NO3-) is one of the substances in liquid waste that can have a significant impact on water systems and human health. Several methods can be used to treat the nitrate contained in the water, such as adsorption, phytoremediation, and wetland treatment. One of its methods was adsorption. The silica was modified with polymer due to its huge carbon chain. This research was focused on optimizing the ability of silica-based materials using PEG by physically coating them since PEG has a long carbon chain that could be transformed into a helix. In this research, the adsorbent will be prepared from modified silica gel with PEG 4000 by physical coating. Several parameters will be observed, including the effect of coating time, silica-PEG ratio, and PEG concentration. The capacity of silica-PEG to absorb NO3- is being studied. The characterization of functional group content in silica-PEG was carried out by Fourier Transform Infrared (FTIR). The study results show that the coating time was 10 minutes with the ratio of silica to PEG of 1:5, and the concentration of PEG used was 15%, indicating the optimum performance of silica-PEG when used as an absorbent, which achieved 84.44 % nitrate removal. An increase in the absorption capacity of silica-PEG demonstrates the ability of silica-PEG as a porous material. It was compared to silica gel without the PEG coating process, which was 9.09% to 84.44%.Abstrak: Semua kegiatan produksi pada akhirnya akan menghasilkan limbah, terutama limbah cair. Limbah cair biasanya akan bermuara di sungai dan berakhir di laut. Salah satu zat dalam limbah cair adalah ion nitrat (NO3-) yang mana dalam jumlah banyak dapat mengganggu sistem perairan dan kesehatan. Beberapa metode dapat digunakan untuk mengolah nitrat yang terkandung dalam air, seperti adsorpsi. Salah satunya dimodifikasi dengan polimer karena memiliki rantai karbon yang besar. Penelitian ini dikonsentrasikan untuk menyelidiki optimalisasi kemampuan silika dengan PEG dengan pelapisan fisik karena PEG memiliki rantai karbon panjang yang dapat bertransformasi menjadi heliks. Dalam penelitian ini, adsorben akan dibuat dari silika gel termodifikasi dengan PEG 4000 dengan pelapisan fisik. Beberapa parameter yang akan diamati antara lain pengaruh waktu pelapisan, rasio silika-PEG, konsentrasi PEG, dan temperatur pelapisan. Kinerja silika-PEG untuk menyerap NO3- diselidiki. Karakterisasi kandungan gugus fungsi pada silika-PEG dilakukan dengan Fourier Transform InfraRed (FTIR). Hasil penelitian menunjukkan bahwa waktu pelapisan adalah 10 menit dengan perbandingan silika dan PEG 1:5, dan konsentrasi PEG yang digunakan adalah 15%, menunjukkan kinerja silika-PEG yang optimum bila digunakan sebagai penyerap NO3-. Kemampuan silika-PEG sebagai bahan berpori dibuktikan dengan peningkatan kapasitas penyerapan silika-PEG dibandingkan silika gel tanpa proses pelapisan PEG.